THE PLACE OF THE OTTOMAN EMPIRE ON THE STAGE OF HISTORY - Abdiyeva Setora Ilyos qizi (Journal Park Publishing, 2023)
It is known from history that there were many Muslim empires in this world. For example, the Caliphate of Baghdad, the Great Amir Timur state, the Baburi Empire, the Ottoman Empire are among them. They were able to build a strong state in different continents of the world, and for centuries they left their names in history. We want to cover the history of the Ottomans.
Keywords: Ottomans, Anatolia, Kay clan, Ertugrul, Osman, Bursa, Constantinople, Ottoman, Murad II, Sultan Ahmed, White Rabbits.